Variability in life expectancy among people with HIV in Brazil by gender and sexual orientation - Paula M. Luz; Hailey Spaeth; Justine A. Scott; Beatriz Grinsztejn; Valdilea G. Veloso; Kenneth A. Freedberg; Elena Losina (Brazilian Journal of Infectious Diseases, 2024)
Introduction: In Brazil, though Antiretroviral Therapy (ART) is available to all, the benefits may not be experienced uniformly. We projected Life Expectancy (LE) for People Living with HIV (PLHIV) in care as currently observed and estimated the impact of guideline-concordant care. Methods: Using a microsimulation model, we projected LE for a cohort of PLHIV and for four population groups: cisgender Men who have Sex with Men (MSM), cisgender Men who have Sex with Women (MSW), Cisgender Women (CGW), and Transgender Women (TGW). Cohort data from Evandro Chagas National Institute of Infectious Diseases/Oswaldo Cruz Foundation (INI/Fiocruz) informed model parameters. We modeled five scenarios: 1) Current care: ART initiation, adherence, and retention in care as currently observed, 2) Guideline-concordant care: immediate ART initiation, full adherence to treatment, and consistent retention in care, 3) Immediate ART initiation with observed adherence to treatment and retention in care, 4) Full adherence to treatment with observed timing of ART initiation and retention in care, and 5) Consistent retention in care with observed timing of ART initiation and adherence. Results: With current care, LE from age 15 would be 45.9, 44.4, 54.2, and 42.3 years, for MSM, MSW, CGW, and TGW. With guideline-concordant care, LE would be 54.2, 54.4, 63.1, and 53.2 years, for MSM, MSW, CGW and TGW, with TGW experiencing the greatest potential increase in LE (10.9 years). When investigating the components of care separately, MSW and CGW would gain most LE with immediate ART initiation, whereas for MSM and TGW consistent retention in care would be most impactful. Conclusions: In settings like INI/Fiocruz, MSW and CGW would benefit most from interventions focused on earlier diagnosis and linkage to care, whereas TGW and MSM would benefit from interventions to sustain engagement in care. Assessment of the HIV care continuum for specific populations should inform care priorities.